Preparation method of antibacterial easy-to-clean glass

Antibacterial coatings containing zinc precursors and film-forming resins were prepared by uniform precipitation method, and combined with physical tempering and hydrophobic coating treatment, the problems of poor adhesion and friction resistance of antibacterial hydrophobic glass coating were solved, and efficient preparation of antibacterial and easy-to-clean glass was achieved.

CN119569350APending Publication Date: 2025-03-07GUANGDONG LEHUA HOME FURNISHING CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593242.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-07

Smart Images

  • Figure CN119569350A_ABST
    Figure CN119569350A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of antibacterial easy-to-clean glass, which comprises the following steps: preparing a zinc-containing precursor by adopting a homogeneous precipitation method, mixing the zinc-containing precursor with water and a dispersing agent, grinding to obtain a zinc-containing precursor dispersion liquid, mixing the zinc-containing precursor dispersion liquid with an alcoholic solution and film-forming resin to obtain an antibacterial coating, and drying to obtain the antibacterial easy-to-clean glass. The preparation method comprises the following steps: coating a glass substrate with an antibacterial coating, drying, carrying out physical toughening treatment to obtain toughened glass, coating the toughened glass with a hydrophobic coating, drying and curing to obtain glass containing a hydrophobic layer, treating the surface of the glass containing the hydrophobic layer with a weak acid solution, and cleaning with water to obtain the antibacterial easy-to-clean glass. According to the invention, the zinc-containing precursor is decomposed into nano-zinc oxide by ingeniously utilizing high temperature of toughening treatment, which is equivalent to that the purposes of decomposing the zinc-containing precursor and toughening are achieved at the same time through one-time heating, so that zinc oxide is better fused with glass, and good antibacterial property can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass production, and in particular to a method for preparing antibacterial and easy-to-clean glass. Background Art

[0002] Applying the corresponding coating on the surface of glass can make it have antibacterial and hydrophobic functions. To achieve the above purpose, there are two common schemes. One is to apply an antibacterial hydrophobic composite coating. This composite coating can be prepared by adding an antibacterial agent to a hydrophobic resin, or by adding an antibacterial agent and a hydrophobic agent to an ordinary resin at the same time. Antibacterial hydrophobic composite coatings usually require the use of film-forming resins, and the thickness is relatively large. Even if inorganic resins are used, their hardness cannot be compared with glass, which makes the coating easily scratched by hard objects. The second is to apply an antibacterial coating first, and then apply a hydrophobic coating that will not cover the antibacterial coating tightly. This hydrophobic coating is usually a nano coating, and it is easy to shield the antibacterial layer if it is too thick; in addition, for physical tempered glass, the antibacterial coating can be made before tempering or after tempering, but the former can only use inorganic antibacterial agents (or antibacterial agents that can form inorganic substances after high temperature decomposition) because of the high temperature of tempering, while the latter can use both inorganic and organic ones. When using the double coating solution, for physically tempered glass, if the antibacterial coating is made after tempering, its adhesion is poor, especially it is not resistant to steel wool friction. If it is made before tempering, since the inorganic antibacterial agent in the antibacterial coating is usually nanoparticles, it is easy to agglomerate and it is difficult to completely disperse it to the original single particle state. This results in a certain proportion of nanoparticles existing in the form of agglomerates on the glass surface after the tempering process, affecting the appearance, although sometimes not too serious.

[0003] Nano zinc oxide is a commonly used inorganic antibacterial agent. It is prepared by direct precipitation method in industry. Direct precipitation method is to add precipitation agent (such as ammonia, sodium hydroxide, sodium carbonate, etc.) that can directly react with zinc ions in zinc salt solution, so that zinc-containing precursor is separated out, and then filtered, washed, dried, calcined, and nano zinc oxide powder can be obtained. However, direct precipitation method directly adds precipitation agent to solution, and there will be the disadvantage of uneven concentration distribution. In addition, when preparing nano zinc oxide by precipitation method, the drying and calcining of its precursor will cause the reunion of particles. In order to alleviate this situation, the last washing before drying will even use ethanol, and the process is not simple. And nano zinc oxide usually needs to be made into dispersion liquid when it is applied in coating, and the reunion caused by the above-mentioned drying and calcining also further increases the difficulty of dispersion. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems in the related art to a certain extent. To this end, the present invention provides a method for preparing antibacterial easy-to-clean glass.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing antibacterial easy-to-clean glass, comprising the following steps:

[0007] S1: preparing a zinc-containing precursor by a uniform precipitation method, mixing the zinc-containing precursor with water and a dispersant, and then grinding to obtain a zinc-containing precursor dispersion;

[0008] S2: mixing the zinc-containing precursor dispersion with an alcohol solution and a film-forming resin to obtain an antibacterial coating;

[0009] S3: coating the antibacterial coating on a glass substrate, and performing physical tempering treatment after drying to obtain tempered glass;

[0010] S4: coating the tempered glass with a hydrophobic coating, and then drying and curing the coating to obtain a hydrophobic layer-containing glass;

[0011] S5: treating the surface of the glass containing the hydrophobic layer with a weak acid solution, and then washing with water to obtain the antibacterial and easy-to-clean glass.

[0012] Among them, the temperature when the zinc-containing precursor loses weight rapidly is 230-280°C, and the temperature when the film-forming resin loses weight rapidly is 350-450°C. Both are completely decomposed at about 500°C.

[0013] In some embodiments of the present invention, in step S1, the preparation method of the zinc-containing precursor is: mixing a zinc salt solution with a precipitant solution, heating and stirring to react, obtaining a suspension, and performing solid-liquid separation on the suspension to obtain the zinc-containing precursor; the zinc salt in the zinc salt solution is at least one of zinc nitrate, zinc sulfate, zinc chloride or zinc acetate, and the precipitant in the precipitant solution is at least one of urea, hexamethylenetetramine, diethanolamine or triethanolamine. Among them, the zinc-containing precursor prepared by urea is generally considered to be basic zinc carbonate ZnCO 3 ·2Zn(OH) 2 , molecular weight 324.2. Further, the amount of the precipitant is 2.5-4 times the zinc element in the zinc salt. Further, the zinc salt is zinc nitrate hexahydrate, the zinc salt solution is made by dissolving zinc nitrate hexahydrate in water, and the mass ratio of zinc nitrate hexahydrate to water is (10-45): (50-60); the precipitant is urea, the precipitant solution is made by dissolving urea in water, and the mass ratio of urea to water is (5-36): (20-30). Further, a dispersant is added to the precipitant solution. Further, the temperature of the heating and stirring reaction is 85-100°C, and the reaction time is 2.5-5h.

[0014] In some embodiments of the present invention, in step S1, the grinding method is ball milling, and the size of the zirconia balls used in the ball milling is 0.1-0.8 mm.

[0015] In some embodiments of the present invention, in step S1, a defoamer is added during the grinding process. Preferably, the defoamer is defoamer BYK-024, which is an organosilicon defoamer that can prevent foaming during grinding.

[0016] In some embodiments of the present invention, in step S1, the dispersant is selected from at least one of dispersant P31, sodium polyacrylate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, polyethylene glycol, or povidone. Preferably, the dispersant is dispersant P31. Dispersant P31 is an anionic surfactant that has a good dispersing effect on inorganic particles and significantly reduces the viscosity of the slurry.

[0017] In some embodiments of the present invention, in step S2, the alcohol solution is composed of ethanol, isopropanol and water in a mass ratio of (70-80): (5-15): (10-20). The alcohol solution can improve the drying speed and leveling performance of the coating. The concentration of the antibacterial coating is low. If the solvent is all water, it dries slowly on the glass during spraying and is easy to shrink, and the film appearance is poor.

[0018] In some embodiments of the present invention, in step S2, the zinc-containing precursor dispersion is first diluted with the alcohol solution to a solid content of 2%-8%, and then the film-forming resin is added, and the mass ratio of the solid content of the zinc-containing precursor dispersion to the solid content of the film-forming resin is 100: (5-50).

[0019] In some embodiments of the present invention, in step S2, the film-forming resin is acrylic resin, water-based polyolefin resin or polyvinyl alcohol. The film-forming resin is preferably water-soluble, does not produce abnormalities when encountering a certain concentration of alcohol, contains less metal salt impurities (for example, the residue of alkali metal salts is unfavorable for the curing of subsequent perfluoropolyether siloxanes), mainly contains carbon, hydrogen and oxygen elements and does not contain or contains less benzene rings (resins containing heteroelements may be difficult to decompose, or are more likely to produce toxic gases when decomposed, but ammonia is allowed to be contained), and acrylic resin, water-based polyolefin resin or polyvinyl alcohol are preferred in the present invention. However, natural polymers, polyurethane resins, silicone resins, etc. are not suitable, and many natural polymers are easily precipitated when encountering alcohol. If starch is not treated otherwise, its solubility in water is not high, and gum arabic may contain potassium salts, and polyurethane resins may produce nitrogen oxides, and silicone resins are difficult to decompose at high temperatures.

[0020] In some embodiments of the present invention, in step S3, the coating amount of the antibacterial coating on the glass substrate is 0.05-0.5 g / m 2 .

[0021] In some embodiments of the present invention, in step S4, before applying the hydrophobic coating, the step further includes plasma treating the tempered glass.

[0022] In some embodiments of the present invention, in step S4, the hydrophobic coating is at least one of perfluoropolyether siloxane, fluorine-modified polysiloxane or polysiloxane. The perfluoropolyether siloxane can form a monolayer hydrophobic coating with a thickness of less than 100 nm, and its molecular end -Si(OR) 3 (R is usually methyl or ethyl) hydrolyzed to form -Si(OH) 3 , and the hydroxyl groups on the surface of glass and zinc oxide dehydrate and condense to form a strong covalent bond, making it durable. The above hydrophobic coatings are all nano coatings, and the molecules all contain siloxane structures, which are similar to the principle of glass bonding and can be selected according to actual needs.

[0023] In some embodiments of the present invention, in step S5, the surface of the glass containing the hydrophobic layer is treated with the weak acid solution by immersion, spraying or roller coating.

[0024] In some embodiments of the present invention, in step S5, the weak acid solution is selected from at least one of citric acid, oxalic acid, acetic acid, lactic acid or formic acid; the mass concentration of the weak acid solution is 0.05%-0.5%. The weak acid solution is an organic weak acid, which is used to remove large particles of zinc oxide. The organic weak acid has a low acid concentration and a short contact time, and will not damage the hydrophobic coating.

[0025] In some embodiments of the present invention, the weak acid solution stays on the surface of the glass containing the hydrophobic layer for 0.5-30 seconds. Preferably, the weak acid solution stays on the surface of the glass containing the hydrophobic layer for 1-5 seconds.

[0026] According to a preferred embodiment of the present invention, there are at least the following beneficial effects:

[0027] 1. The zinc-containing precursor prepared by the uniform precipitation method of the present invention is directly ground and dispersed into a dispersion liquid by adding water, thereby omitting the drying and calcining steps of the zinc-containing precursor, and further agglomeration of particles can be avoided. Subsequently, the zinc-containing precursor dispersion liquid is mixed with a film-forming resin to prepare an antibacterial coating, and the antibacterial coating is coated on a glass substrate and then tempered. The high temperature of the tempering treatment is cleverly used to decompose the zinc-containing precursor into nano zinc oxide, which is equivalent to achieving the purpose of decomposing the zinc-containing precursor and tempering at the same time in one heating. Not only does it simplify the process, but the precursor in the antibacterial coating is coated with a film-forming resin, which can largely avoid agglomeration during high-temperature heating. In addition, the glass will soften during the tempering treatment, and part of the volume of the nano zinc oxide will be embedded in the substrate, and the original size of the nano zinc oxide is less than 50nm. The above-mentioned anti-agglomeration measures enable zinc oxide to better fuse with the glass, and even if it is damaged by friction or water bath, it can still maintain good antibacterial properties.

[0028] 2. After the hydrophobic coating is cured, a dilute weak acid is applied again, which can remove the large particles of zinc oxide that affect the appearance, making the appearance better, and will not have an adverse effect on the small particles of zinc oxide and the hydrophobic coating that are invisible to the naked eye, and the contact angle of the glass is increased. Weak acid treatment can only be carried out after the hydrophobic coating is applied. If it is carried out before, some small particles of zinc oxide will be removed because there is no coverage of the hydrophobic coating, resulting in a decrease in the antibacterial ability of the final product. It is generally believed that acid and alkali will have an adverse effect on the hydrophobic coating, so the coating is rarely post-processed with acid and alkali, but the acid concentration of the present invention is low, and the contact time is short, and the coating will not be damaged. In addition, the effect of weak acid treatment also depends on the previous nano process to a certain extent. If the zinc oxide size is too large or agglomerates seriously, it can not be well embedded in the glass substrate, and the residence time of the weak acid solution is very short, it can remove the part exposed to the substrate, but if it is exposed too much, it cannot be removed in a short time. Therefore, nanoization is crucial, and the zinc oxide size is fine enough, most of it is embedded in the substrate, and only a very small part is exposed, and it is easy to remove with weak acid.

[0029] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0031] Figure 1 This is a schematic structural diagram of the antibacterial easy-to-clean glass according to Example 1 of the present invention;

[0032] Figure 2 This is a SEM image of Example 1 of the present invention before roller coating of citric acid;

[0033] Figure 3This is a comparison diagram of the actual objects before and after citric acid treatment in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0035] Example 1

[0036] This embodiment prepares an antibacterial and easy-to-clean glass, and the specific process is as follows:

[0037] (1) Preparation of nano antibacterial coating

[0038] ① Weigh 21.4 parts (by mass) of zinc nitrate hexahydrate, add 54.5 parts of pure water to dissolve, obtain a zinc nitrate solution, and heat to 95°C;

[0039] ② Weigh 15.1 parts of urea, add 25 parts of pure water to dissolve, and add 0.2 parts of dispersant P31 (solid content 40%, Fuke Technology (Suzhou) Co., Ltd.). When the solution temperature returns to room temperature, pour it into the above zinc nitrate solution at one time under stirring conditions, then close the container, maintain the temperature in ① and continue stirring for 4 hours to obtain a suspension;

[0040] ③ Cool the suspension from the previous step, centrifuge at 6000 rpm for 5 min, remove the supernatant, add pure water to the obtained solid, stir and wash, centrifuge at 6000 rpm for 5 min, remove the supernatant, repeat once, and obtain 50.7 parts of the centrifugal residue, i.e., the zinc-containing precursor (solid content 14%);

[0041] ④ Add water to the above centrifugal residue to dilute it to a mass fraction of 11%, add 0.2 parts of dispersant P31, stir evenly and then ball mill, the zirconium oxide ball size is 0.5mm, the rotation speed is 2000rpm, the ball milling time is 1h, add 0.06 parts of BYK-024 defoamer, continue grinding for 0.5h, and obtain a zinc-containing precursor dispersion;

[0042] ⑤ Dilute the zinc-containing precursor dispersion with a mixed solution of ethanol: isopropanol: water = 75:10:15 (volume ratio) to a solid content of 5%, add acrylic resin (MR1806W, solid content 40%, Guangdong Keding Functional Materials Co., Ltd.) so that the mass ratio of the solid content of the zinc-containing precursor dispersion to the solid content of the acrylic resin is 100:15, and obtain the nano antibacterial coating.

[0043] (2) Preparation of coating

[0044] ① Clean the glass substrate and spray the nano antibacterial coating with a spraying amount (dry weight) of 0.15g / m 2 After the surface is dried, physical tempering treatment is performed and the glass is cooled to below 50°C to obtain tempered glass;

[0045] ② The tempered glass was plasma treated, and then sprayed with perfluoropolyether siloxane solution (AF-1, Shenzhen Ruidun Nano New Materials Co., Ltd.), and cured at 150°C for 0.5h after the surface was dried;

[0046] ③ Roller-coat the glass in the previous step with a 0.2% citric acid solution. The citric acid solution stays on the glass surface for 3 seconds, and then rinses it with water to obtain antibacterial and easy-to-clean glass.

[0047] Example 2

[0048] This embodiment prepares an antibacterial and easy-to-clean glass, and the specific process is as follows:

[0049] (1) Preparation of nano antibacterial coating

[0050] ① Weigh 15 parts (by mass) of zinc nitrate hexahydrate, add 54.5 parts of pure water to dissolve, obtain a zinc nitrate solution, and heat to 95°C;

[0051] ② Weigh 10.6 parts of urea, add 25 parts of pure water to dissolve, and add 0.2 parts of dispersant P31 (solid content 40%, Fuke Technology (Suzhou) Co., Ltd.). When the solution temperature returns to room temperature, pour it into the above zinc nitrate solution at one time under stirring conditions, then close the container, maintain the temperature in ① and continue stirring for 4 hours to obtain a suspension;

[0052] ③ Cool the suspension from the previous step, centrifuge at 6000 rpm for 5 min, remove the supernatant, add pure water to the obtained solid, stir and wash, centrifuge at 6000 rpm for 5 min, remove the supernatant, repeat once, and obtain 31.9 parts of the centrifugal residue, i.e., the zinc-containing precursor (solid content 14.5%);

[0053] ④ Add water to the above centrifugal residue to dilute it to a mass fraction of 11%, add 0.13 parts of dispersant P31, stir evenly and then ball mill, the zirconium oxide ball size is 0.5mm, the rotation speed is 2000rpm, the ball milling time is 1h, add 0.04 parts of BYK-024 defoamer, continue grinding for 0.5h, and obtain a zinc-containing precursor dispersion;

[0054] The remaining steps are the same as in Example 1.

[0055] Example 3

[0056] In this embodiment, an antibacterial and easy-to-clean glass is prepared. Except for the last step in which the citric acid solution is retained for 30 seconds, the remaining steps are the same as those in Embodiment 1.

[0057] Comparative Example 1

[0058] This comparative example prepares an antibacterial and easy-to-clean glass, which is different from Example 1 in that the last step of roller coating of the citric acid solution in Example 1 is omitted, and the rest is the same as Example 1.

[0059] Comparative Example 2

[0060] This comparative example prepares an antibacterial and easy-to-clean glass. The difference from Example 1 is that a nano antibacterial coating containing ZnO is used. The specific process is as follows:

[0061] ① Take a nano zinc oxide dispersion (DXN-HF30S, solid content 30%, Darcinon Nanotechnology (Changzhou) Co., Ltd.), dilute it to a solid content of 5% with a mixed solution of ethanol: isopropanol: water = 75:10:15 (volume ratio), stir evenly, add acrylic resin, so that the mass ratio of the solid content of the nano zinc oxide dispersion to the solid content of the resin is 75:15, stir evenly, and obtain a nano antibacterial coating;

[0062] ② Clean the glass substrate and spray the nano antibacterial coating with a spraying amount (dry weight) of 0.15g / m 2 , after surface drying, physical tempering is performed, and the glass is cooled to below 50°C to obtain tempered glass;

[0063] ③ Plasma treatment was performed on the tempered glass, and then perfluoropolyether siloxane solution was sprayed on the tempered glass, and after the surface was dried, the glass was cured at 150°C for 0.5h;

[0064] ④ Roller-coat the glass in the previous step with a 0.2% mass concentration of citric acid solution. The residence time of the citric acid solution on the glass surface is 3s, and then rinse it with water to obtain antibacterial and easy-to-clean glass.

[0065] Comparative Example 3

[0066] This comparative example prepares an antibacterial and easy-to-clean glass. The difference from Example 1 is that a zinc-containing precursor is prepared by a direct precipitation method. The specific process is as follows:

[0067] ① Add 0.5 g of P31 dispersant to 0.4 mol / L × 0.5 L zinc nitrate solution, stir evenly, then dropwise add 0.72 mol / L × 0.5 L sodium hydroxide solution under stirring, stir at room temperature for 30 min to obtain a suspension;

[0068] ② Centrifuge the suspension at 6000 rpm for 5 min, remove the supernatant, add pure water to the solid, stir and wash, centrifuge at 6000 rpm for 5 min, remove the supernatant, repeat once, and obtain the centrifugal residue;

[0069] ③ Add water to the above centrifugal residue to dilute it to a mass fraction of 11%, add 0.5g of P31 dispersant, stir evenly and then ball mill, the zirconium oxide ball size is 0.5mm, the speed is 2000rpm, the time is 1h, add 0.15g of BYK-024 defoamer, continue grinding for 0.5h, and obtain a zinc-containing precursor dispersion;

[0070] ④ Dilute the zinc-containing precursor dispersion with a mixed solution of ethanol: isopropanol: water = 75:10:15 (volume ratio) to a solid content of 5%, add acrylic resin so that the mass ratio of the solid content of the zinc-containing precursor dispersion to the resin solid content is 92:15, stir evenly, and obtain a nano antibacterial coating.

[0071] The remaining steps are the same as in Example 1.

[0072] Test example

[0073] This test example tests the performance of the antibacterial easy-to-clean glass prepared in the examples and comparative examples.

[0074] Contact angle: tested according to JC / T 2168-2013;

[0075] Antibacterial rate: tested in accordance with GB / T 31402-2015;

[0076] Friction method: Use #0000 steel wool pad to rub the sample and square grinding head (1×1cm 2 ), reciprocating friction, total load 1Kg (i.e. pressure 100KPa), friction 10,000 times (one forward plus one reverse counts as one time), frequency 30 times / min, stroke 50mm (one forward or one reverse distance);

[0077] Water bath method: Soak in 50℃ tap water for 28 days, then rinse and dry.

[0078] The performance test results of the embodiments and comparative examples are shown in Table 1.

[0079] Table 1 Performance test

[0080]

[0081] As can be seen from Table 1, the haziness of Example 2 when observed at a close distance at an oblique angle to light is more obvious than that of Example 1. This is because the absolute concentrations of zinc nitrate and urea in Example 2 are reduced, but the relative concentrations remain unchanged, which will cause the particle size of the zinc-containing precursor to become larger. Comparative Example 1 has not been roller-coated with citric acid, and has a hazy feeling when observed at a close distance at an oblique angle to light, indicating that roller-coating with citric acid can improve the appearance of glass. Comparative Example 2 uses a nano-antibacterial coating containing ZnO. The zinc oxide particles in the antibacterial coating are easy to agglomerate during tempering, and it is difficult to completely disperse them to the original single particle state, which has a certain impact on the appearance of the glass and the adhesion of the antibacterial coating. Comparative Example 3 uses a direct precipitation method to prepare a zinc-containing precursor, and its nano-ization and uniformity are not as good as the uniform precipitation method of Example 1, and the antibacterial coating still has agglomeration phenomenon.

[0082] Figure 3 This is a comparison of the objects before and after the citric acid treatment in Example 1. The picture needs to be taken at a special angle. When observed at a normal angle with the naked eye, it is basically the same as the original glass, but when observed at a close distance at an angle, it has a hazy feeling. It can be seen in the picture that the position treated with acid in the upper left corner is completely transparent, while the other positions are not treated with acid and appear hazy.

[0083] In general, the antibacterial hydrophobic glass produced by the present invention is transparent in appearance, and when observed at a close distance at an oblique angle to light, there is no haziness, just like the original glass; the hydrophobicity and antibacterial properties are good before and after destructive testing, meeting the durability requirements, and is particularly suitable for occasions where antibacterial hydrophobicity is required, such as shower rooms.

[0084] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing antibacterial easy-to-clean glass, characterized in that: The following steps are involved: S1: preparing a zinc-containing precursor by a uniform precipitation method, mixing the zinc-containing precursor with water and a dispersant, and then grinding to obtain a zinc-containing precursor dispersion; S2: mixing the zinc-containing precursor dispersion with an alcohol solution and a film-forming resin to obtain an antibacterial coating; S3: coating the antibacterial coating on a glass substrate, and performing physical tempering treatment after drying to obtain tempered glass; S4: coating the tempered glass with a hydrophobic coating, and then drying and curing the coating to obtain a hydrophobic layer-containing glass; S5: treating the surface of the glass containing the hydrophobic layer with a weak acid solution, and then washing with water to obtain the antibacterial and easy-to-clean glass.

2. The preparation method according to claim 1, characterized in that: In step S1, the preparation method of the zinc-containing precursor is: mixing a zinc salt solution and a precipitant solution, heating and stirring to react, obtaining a suspension, and performing solid-liquid separation on the suspension to obtain the zinc-containing precursor; the zinc salt in the zinc salt solution is at least one of zinc nitrate, zinc sulfate, zinc chloride or zinc acetate, and the precipitant in the precipitant solution is at least one of urea, hexamethylenetetramine, diethanolamine or triethanolamine.

3. The preparation method according to claim 1, characterized in that: In step S2, the alcohol solution is composed of ethanol, isopropanol and water in a volume ratio of (70-80):(5-15):(10-20).

4. The preparation method according to claim 1, characterized in that: In step S2, the zinc-containing precursor dispersion is first diluted with the alcohol solution to a solid content of 2%-8%, and then the film-forming resin is added. The mass ratio of the solid content of the zinc-containing precursor dispersion to the solid content of the film-forming resin is 100:(5-50).

5. The preparation method according to claim 1, characterized in that: In step S2, the film-forming resin is acrylic resin, water-based polyolefin resin or polyvinyl alcohol.

6. The preparation method according to claim 1, characterized in that: In step S3, the coating amount of the antibacterial coating on the glass substrate is 0.05-0.5 g / m 2 .

7. The preparation method according to claim 1, characterized in that: In step S4, before applying the hydrophobic coating, the tempered glass is further subjected to plasma treatment.

8. The preparation method according to claim 1, characterized in that: In step S4, the hydrophobic coating is at least one of perfluoropolyether siloxane, fluorine-modified polysiloxane or polysiloxane.

9. The preparation method according to claim 1, characterized in that: In step S5, the weak acid solution is selected from at least one of citric acid, oxalic acid, acetic acid, lactic acid or formic acid; and the mass concentration of the weak acid solution is 0.05%-0.5%.

10. The preparation method according to claim 1, characterized in that: The weak acid solution stays on the surface of the glass containing the hydrophobic layer for 0.5-30 seconds.